Evaluation of a Fermentation Source of 25-hydroxycholecalciferol in Broiler Diets - Goodgame, S.D.; Mussini, F.J.; Lu, C.; Bradley, C.D.; Watkins, S.E.; Waldroup , P.W. (International Journal of Poultry Science, 2011)
After a seven day depletion period of vitamin D supplementation beginning on day of hatch, male chicks of a commercial broiler strain were placed on diets supplemented with either a commercial source of 25-hydroxycholecalciferol (25-OH-D3) or a new source derived from fermentation. Levels of 0, 2.5, 5, 10, 20, 40, 60 and 80 μg/kg of each source were added to a common basal diet that was considered as marginal in calcium and phosphorus content. Each diet was fed to six pens of five birds each. Birds were then grown to 21 d of age at which time body weight and feed consumption were determined. All birds were euthanized by CO2 inhalation and all toes were removed and ashed. The right tibia was subjected to bone ash determination while the left tibia was subjected to break force analysis. Analysis of the data indicated no significant differences in performance between chicks fed the two sources of 25-OH-D3 (p